Schmidt's Syndrome: An Uncommon Cause of Spontaneous Hypoglycemia - Zacharia, George Sarin; Jacob, Anu; Bose, Binu Mary (Avicenna Journal of Medicine, 2024)
Schmidt's syndrome, or autoimmune polyendocrine syndrome type 2 (APS-2), is an uncommon disorder characterized by the co-occurrence of autoimmune thyroiditis and adrenalitis. APS-2 is defined as a combination of Addison's disease, autoimmune thyroid disease, and/or type 1 diabetes mellitus. It is an autosomal dominantly inherited polygenic disorder with incomplete penetrance; the candidate genes include but are not limited to HLA-DR3, HLA-DR4, CTLA-4, PTPN22, and CD25-IL-2. Autoimmune thyroiditis, often Hashimoto's disease, results in hypothyroidism. Primary adrenal failure results in enhanced secretion of adrenocorticotrophic hormone melanocyte and co-secretion of melanocyte-stimulating hormone, contributing to hyperpigmentation. Mineralocorticoid deficiency results in salt wasting, fatigue and cramps, postural hypotension, and hyperkalemia. Cortisol, an insulin counter-regulatory hormone, plays a pivotal role in maintaining euglycemia; deficiency predisposes to the development of hypoglycemia. We here report a rare presentation of Schmidt's syndrome as hypoinsulinemic hypoglycemia in a middle-aged male patient. Management includes treatment of acute hypoglycemic episodes with glucose or glucagon, long-term glucocorticoids and mineralocorticoids for adrenal insufficiency, and thyroid hormone supplements for hypothyroidism. This case report and brief overview aim to contribute to the scientific understanding of Schmidt's syndrome/APS-2. Additionally, here we briefly outline the diagnostic challenges in hypoglycemia evaluation, including the utilization of Whipple's triad and the gold standard supervised 72-hour fast and evaluation for primary adrenal and thyroid insufficiencies.
Keywords: Schmidt's syndrome; APS-2; polyendocrine syndrome; Addison's disease; hypoglycemia; hypothyroidism